Mixed Convection and Nonlinear Radiation in the Stagnation Point Nanofluid flow towards a Stretching Sheet with Homogenous-Heterogeneous Reactions effects. (2015) - Das, M.; Mahatha, B.K.; Nandkeolyar, R.
Abstract: The effect of homogeneous-heterogeneous reactions on the steady two dimensional mixed convection stagnation point boundary layer flow of an incompressible, viscous, electrically conducting, nonlinear radiative heat transfer and chemically reacting copper- water nanofluid toward a linear stretching sheet are numerically investigated in this paper. The spectral local linearization method (SLLM) is used to find the solution for the fluid velocity, fluid temperature and species concentration. Such type of nanofluid flow model are usefull in many engineering process such as insulation system, heat exchanger devices and chemical catalytic.